Global warming’s “Six Americas” among Iowa farmers: exploring differential attitudes towards climate change and agriculture - Laurie W. Nowatzke; J. G. Arbuckle (npj Climate Action)
Abstract Agricultural production in the U.S. Midwest faces pressure to adapt to the negative impacts of climate change (e.g., extreme precipitation, drought) and to mitigate farms’ greenhouse gas emissions. Research has found that farmer attitudes toward and concern about climate change are highly variable and heterogenous. To explore variation in attitudes towards climate change, we have utilized the Six Americas Super Short Survey (SASSY), a four-item questionnaire that types individuals into six “types” based on their climate change beliefs and attitudes, with 1,039 Iowa farmers. This novel application of the SASSY typology method found that 22% of Iowa farmers aligned with the dismissive type, 20% were doubtful, 7% were disengaged, 23% were cautious, 16% were concerned, and 12% were alarmed. We also explored variation in farmers’ attitudes towards agricultural impacts and risks; we find that the SASSY correlates with attitudes towards more specific agricultural issues as they relate to climate change.